2023
DOI: 10.3389/fncom.2023.1132160
|View full text |Cite
|
Sign up to set email alerts
|

Hyperscanning fNIRS data analysis using multiregression dynamic models: an illustration in a violin duo

Abstract: IntroductionInterpersonal neural synchronization (INS) demands a greater understanding of a brain's influence on others. Therefore, brain synchronization is an even more complex system than intrasubject brain connectivity and must be investigated. There is a need to develop novel methods for statistical inference in this context.MethodsIn this study, motivated by the analysis of fNIRS hyperscanning data, which measure the activity of multiple brains simultaneously, we propose a two-step network estimation: Tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Recent research has suggested that the brain networks associated with artistic and social functions may overlap, which thus has significant practical implications for mental health (van Leeuwen et al, 2022). In accordance, aesthetic experiences entrail social understanding, which involves perspective taking, belief attribution, imagination, and other cognitive processes relevant to the theory of mind (ToM) or mentalizing brain network, including the temporoparietal junction, and regions of the DMN (mainly the medial anterior and posterior cortices) (Beudt & Jacobsen, 2015;Liu et al, 2021;Nascimento et al, 2023;Rojiani et al, 2018;van Leeuwen et al, 2022). Relatedly, the flexible configuration of neural networks has been suggested to be sensitive to individuals' desires, expectations, goals, mood, context, and accumulated lifetime experiences with art (Casale et al, 2023;Nadal & Chatterjee, 2019).…”
Section: The Aesthetic Brain Network Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has suggested that the brain networks associated with artistic and social functions may overlap, which thus has significant practical implications for mental health (van Leeuwen et al, 2022). In accordance, aesthetic experiences entrail social understanding, which involves perspective taking, belief attribution, imagination, and other cognitive processes relevant to the theory of mind (ToM) or mentalizing brain network, including the temporoparietal junction, and regions of the DMN (mainly the medial anterior and posterior cortices) (Beudt & Jacobsen, 2015;Liu et al, 2021;Nascimento et al, 2023;Rojiani et al, 2018;van Leeuwen et al, 2022). Relatedly, the flexible configuration of neural networks has been suggested to be sensitive to individuals' desires, expectations, goals, mood, context, and accumulated lifetime experiences with art (Casale et al, 2023;Nadal & Chatterjee, 2019).…”
Section: The Aesthetic Brain Network Dynamicsmentioning
confidence: 99%
“…INS is viewed as an entrainment phenomenon, shown to be promoted and enhanced by real-time interactive behavior (Koul et al, 2023). Neural synchrony has consistently been reported during joint artistic engagement, such as while creating, performing or listening to music (Abrams et al, 2013;Babiloni et al, 2012;Liu et al, 2021;Müller et al, 2013;Nascimento et al, 2023;Osaka et al, 2015;Ramírez-Moreno et al, 2023;Rojiani et al, 2018;Sachs et al, 2020;Sänger et al, 2012;Zamm et al, 2018), after musical interaction (Khalil et al, 2022), while performing dramatic scenes (Greaves et al, 2022), in collaborative drawing (da Cruz Monteiro et al, 2022), while viewing a dance performance (Herbec et al, 2015;Jola et al, 2013), and in shared movement (Reddish et al, 2013;Varlet et al, 2020).…”
Section: Interactive Relational Aesthetic Experiences At the Core Of ...mentioning
confidence: 99%